Library makerspace in Turkey: Public and university libraries - Güneş, Ayşenur; Canatar, Mehmet (SAGE Publications, 2022)
This study is intended to determine the developments in Turkey and to reveal the quality of the libraries that offer makerspace service. In the light of the data, obtained from the Ministry of Culture and Tourism at the time of the study, one university library and three public libraries where this service was offered in Turkey were examined. However, one public library was examined in detail within the scope of the study. Qualitative research methods were used, and the data collected by the semi-structured interview technique were evaluated with the descriptive analysis method. According to the results not much progress has been observed in Turkey regarding the services offered by the library makerspace. The fact that the public libraries evaluated in this study offer only one service, however, shows that they cannot fully realize the maker philosophy.
Keywords: 4. Education